Interest Rate Dan Political Connection Pada Harga Saham - Farah Margaretha Leon; Putri (JRB-Jurnal Riset Bisnis, 2018)
Background of Research related with share price as indicator in assessing firm’s financial condition. So that investors need to know which factors affecting share price of a company. Purpose of Research is to obtain empirical evidence about factors affecting share price with interest rate and political connection as moderating variables. Research Method adopted in this research is multiple regressions. Population in this study is companies which consistently listed in Indonesia Stock Exchange from 2012 until 2016. Technique use for taking sample is purposive sampling. There are 63 companies selected as final sample. Result Obtained shows that dividend, earnings per share (EPS), return on equity (ROE) and profit after tax (PAT) partially affected share price of a company. On the other hand, retention ratio did not affect share price of a company. Interest rate as moderating variable has moderation effect to dividend, ROE and PAT but no moderate effect found with RR and EPS. Political Connection as second moderating variable has moderation effect to EPS and PAT but did not has moderate effect to dividend, RR and ROE. Managerial Implication hopefully this research could give information for managers that dividend not always give positive impact to share price. If a company wants to increase their share price, they should pay attention to amount declared as EPS, ROE and PAT because these three variables give positive impact to share price of a company.